Magmatic‐Hydrothermal Mineralization Sequence in Xinlu Ore Field, Guangxi, South China: Constraints from Zircon U‐Pb, Molybdenite Re‐Os, and Muscovite Ar‐Ar Dating. Issue 4 (21st August 2019) - Feng, Yangyang; Feng, Zuohai; Fu, Wei; Kang, Zhiqiang; Jiang, Jian; Guo, Along; Wang, Xi; Feng, Meng; Wang, Chunzeng
Abstract: The Xinlu Sn‐polymetallic ore field is located in the western Nanling Polymetallic Belt in northeastern Guangxi, South China, where a number of typical skarn‐, hydrothermal vein‐type tin deposits have developed. There are two types of Sn deposits: skarn‐type and sulfide‐quartz vein‐type. The tin mineralizations mainly occur on the south side of the Guposhan granitic complex pluton and within its outer contact zone. To constrain the Sn mineralization age and further understand its genetic links to the Guposhan granitic complex, a series of geochronological works has been conducted at the Liuheao deposit of the ore field using high‐precision zircon SHRIMP U‐Pb, molybdenite Re‐Os, and muscovite Ar‐Ar dating methods. The results show that the biotite‐monzogranite, which is part of the Xinlu intrusive unit of the Guposhan complex pluton, has a SHRIMP U‐Pb zircon age of 161.0 ± 1.5 Ma. The skarn‐type ore has a 40 Ar‐ 39 Ar muscovite plateau age of 160 ± 2 Ma (same as its isochron age), and the sulfide‐quartz vein‐type ore yields an Re‐Os molybdenite isochron age of 154.4 ± 3.5 Ma. The magmatic‐hydrothermal geochronological sequence demonstrated that the hydrothermal mineralization took place immediately following the emplacement of the monzogranite, with the skarn metasomatic mineralization stage predating the sulfide mineralization stage. Geochronologically, we have compared this ore field with 26 typical Sn deposits distributed along the Nanling Polymetallic Belt, leading to the suggestion of the magmatic‐metallogenic processes in the Xinlu ore field (ca. 161–154 Ma) as a component of the Early Yanshanian large‐scale Sn‐polymetallic mineralization event (peaked at 160–150 Ma) in the Nanling Range of South China. Petrogenesis of Sn‐producing granite and Sn‐polymetallic mineralization were probably caused by crust–mantle interaction as a result of significant lithospheric extension and thinning in South China in the Late Jurassic. Abstract : Compared with 26 typical Sn deposits show that the magmatic‐metallogenic processes in the Xinlu ore field (ca. 161‐154 Ma) as a component of the Early Yanshanian large‐scale Sn‐polymetallic mineralization event (peaked at 160‐150 Ma) in the Nanling Range of South China.